Implementing Edupreneurship in Early Childhood Education: Enhancing Holistic Development through Creative Learning Projects - Dedeh Komalasari; Darmayanti; Lena Ahdiani (Ilmu Inovasi Nusantara, 2025)
Early Childhood Education requires learning aids, including instructional tools and media for delivering messages, to support children's need for concrete learning experiences. Teacher creativity and innovation are crucial, and one approach that enhances this is edupreneurship. This study aims to describe the implementation of edupreneurship by teachers and analyze its positive impact on early childhood development. Using a qualitative descriptive method, the research explored how teachers implement edupreneurship to support the learning process and stimulate child development in various domains. The learning activities were conducted through project-based approaches such as the Children's Market and Kartini Day Parade. In preparing for these events, teachers created learning media using recycled materials like cardboard, newspapers, plastic, and fabric scraps. The process involved both parents and children as active participants in the learning experience. Assessment indicators referred to four areas of child development: cognitive, language, physical-motor, and social-emotional. Findings indicate that through the edupreneurship approach, teachers acted not only as instructors but also as facilitators who effectively stimulated children's development. Children showed significant improvement in logical-mathematical thinking and problem-solving (cognitive), increased vocabulary and expressive ability (language), active participation in movement and role-play (physical-motor), and better emotional regulation and social interaction (social-emotional). Edupreneurship thus supports meaningful and holistic learning while enhancing both teacher professionalism and child development